Influence of Specified vis-a-vis Commercial Mineral Mixture on Haemato-Biochemical Parameters and Serum Mineral Concentration in Crossbred Calves - Bhatt, Shriya; Mondal, Bidhan C; Palod, Jyoti; Kumar, Anil; Kumar, Ripusudan (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
A study was conducted to discern the effects of supplementation of areas specific mineral mixture in comparison to commercial mineral mixture on the haemato-biochemical and mineral profile of growing crossbred calves. Feeding trial was conducted for 120 days on 15 one-week-old calves that were randomly assigned to 3 equal groups, each of 5 heads. Group 1 received a basal diet (milk, calf starter, green fodder as per NRC, 2001). Group 2 received a basal diet with commercial mineral mixture (Agrimin) supplementation, and Group 3 received a basal diet with areas specified mineral mixture (containing ionic mineral salts like dicalcium phosphate 99.40% and copper sulphate 0.6%). All calves were fed whole milk, calf starter containing broken wheat, soyabean chura and deoiled rice bran, and green fodder (berseem grass, oat and mustard). Milk was discontinued after 2 months. Blood samples were collected at the 1st, 8th, and 16th weeks of age of calves for haemato-biochermical analysis. Throughout the trial, there were no significant (p>0.05) differences in haematological parameters. During 1st week, biochemical parameters did not differ significantly among the groups. At 8th week, group 3 showed a significant (p<0.05) decrease in blood glucose, while groups 2 and 3 displayed significantly (p<0.05) higher total protein and SGOT levels. At 16th week, group 2 and 3 exhibited significantly (p<0.05) higher glucose and albumin levels. Mineral concentrations did not differ significantly (p>0.05) at 1st week, while significantly (p< 0.05) increased during the 8th and 16th weeks. In general, specified mineral supplementation in young calves resulted in numerically improvements in Hb, PCV, and significant improvement in glucose, total protein, albumin, SGOT, calcium, phosphorus and copper concentration, while remaining within normal physiological range. Hence, specified mineral mixture can be safely incorporated into the calves’ ration without adversely affecting their blood biochemistry and mineral profiles.